Mathematical Modelling of the Growth of Burkholderia sp. on Glyphosate - Manogaran, Motharasan; Yasid, Nur Adeela; Ahmad, Siti Aqlima (Journal of Environmental Microbiology and Toxicology, 2018)
Glyphosate is an agricultural herbicide with usage in the amounts of thousands of tonnes per year in Malaysia. In certain soils, glyphosate can persist for months and its removal through bioremediation is the most economical and practical. A glyphosate-degrading bacterium has been isolated from contaminated soil. The growth of the bacterium on glyphosate as the sole phosphorous source shows classical sigmoidal profile. Important growth constants can be reliably obtained through nonlinear regression modelling using growth models such as logistic, Gompertz, Richards, Schnute, Baranyi-Roberts, Von Bertalanffy, Buchanan three-phase and the Huang models. The modified Gompertz model was chosen as the best model based on statistical tests such as root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), bias factor (BF), accuracy factor (AF) and corrected AICc (Akaike Information Criterion). Novel constants obtained from the modelling exercise would be useful for further secondary modelling implicating the effect of media conditions and other factors on the growth of this bacterium on glyphosate. The fitted value of maximal growth rate showed a decline when the concentration of glyphosate was increased indicating substrate inhibition. The results from this work can be further used in secondary modelling exercises.